Tradisi, Seni, dan Beladiri (Kajian Historis Perkembangan Perguruan Silat Maung Pande di Kecamatan Menes Kabupaten Pandeglang tahun 2005-2020) - Rosdiana, Hilma; Wibowo, Tubagus Umar Syarif Hadi; Nashar, Nashar (Universitas Galuh, 2025)
This research aims to examine the dynamics of the Maung Pande martial arts school in Menes Subdistrict, Pandeglang Regency, from 2005 to 2020, and to explain the functions of Pencak Silat as an art, tradition, and martial practice. The research method used is the historical method, which includes heuristics, criticism, interpretation, and historiography. The findings show that the Maung Pande martial arts school was founded in 1975 by Abah Kemed and Abah Asmail, based on the Cimande style of silat, with the purpose of fostering silat practitioners in Pandeglang Regency in particular. The term Maung Pande means “Excellent Human of Pandeglang” and the school has grown to 240 branches across Indonesia, with 32 branches in Pandeglang Regency and 3 in Menes Subdistrict. Since its official establishment in 2005 until 2020, Pencak Silat in the Maung Pande school has undergone a transformation, serving as a medium for sports, spiritual and mental education, martial knowledge, an art with aesthetic movement values, as well as community entertainment during weddings, circumcision ceremonies, and cultural festivals. This reflects the transformation of the functions of the Maung Pande martial arts school. However, in 2020 the school experienced a decline due to the Covid-19 pandemic, which hampered its activities as a result of large-scale social restrictions aimed at preventing the spread of the virus.